Effect Of Tai Chi Qigong On Aerobic Capacity In Elderly Examined By Using 6-Minute Walk Test - Rachman, Maria J; Kurniawati, Patricia M; Nugroho, Nunung (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2019)
Introduction: The derivation of aerobic capacity affects elderly greatly, that is why prevention is needed. One of the example is exercise, such as Tai Chi. Aim: This research is a pre-experimental study to discover the effect of Tai Chi on aerobic capacity in elderly. Methods: Tai Chi intervention is given over the course of 8 weeks or 40 meetings, with a maximun of 5 times a week meetings, each has duration of 60 minutes. Qigong style Tai Chi is used. Aerobic capacity is rated by using 6-Minute Walk Test (6MWT) which followed by counting in the result to a regression formula to get VO2max. A total of 17 samples are succeed to satisfy the inclusion and exclusion criterias, as well as completing the whole research with more than 75% exercise attendance. The data retrieval of 6MWT is done before intervention, on the fourth week, and after intervention. Results: There is a derivation of aerobic capacity in elderly, from 25,103070 ml/kg/min (before intervention) to 24,4344 ml/kg/min (fourth week) unsignificantly (p=0,234). There is an escalation of aerobic capacity in elderly from 24,4344 ml/kg/min (fourth week) to 25,248976 ml/kg/min (after intervention) significantly (p=0,04). There is an escalation of aerobic capacity in elderly, from 25,103070 ml/kg/min (before intervention) to 25,248976 ml/kg/min (after intervention), but it is unsignificantly escalated (p=0,800). Conclusion: Tai Chi Qigong has not give a significant effect on aerobic capacity in elderly during the 8-weeks intervention or 40 meetings.